One new Gomphonema (Bacillariophyta) species from Yunnan Province, China - Jiang, Ziyi; Liu, Yan; Kociolek, John Patrick; Fan, Yawen (Phytotaxa, 2018)
During an investigation of the diatom biodiversity of Yunnan Province, one new Gomphonema species was observed from a plateau wetland / nature reserve area associated with Lashi Lake. The new species resembles members of the Gomphonema acuminatum complex, possessing a distinctive outline where the tumid center of the valve is as wide or wider than the headpole. The swollen middle portion of the valve extends more towards both poles than in other taxa in this species group. We describe the morphological features of the new taxon based on LM and SEM observations. This is another report of a new Gomphonema species from Yunnan Province, China; recently a new taxon in this species complex was also described from this Province.